ASSESSMENT OF ANTIMICROBIAL ACTIVITY OF NOVEL DISINFECTANT BASED ON PEROXYGEN/BIGUANIDE/ALCOHOL COMBINATION - Mostafa Essam Eissa (Indonesian Journal of Pharmacy, 2014)
A new disinfectant formula based on combination of Hydrogen peroxide 0.6g%, Chlorohexidine gluconate 0.5g% and Isopropanol 70.5g% was investigated to be used as broad spectrum disinfectant in an attempt to make better control over microbial bioburden in clean area during critical processes. A proper neutralization method was first implemented using combi-nation of dilution 1:10 (v/v) and chemical inactivation method using LBC3T then disinfectant efficacy study was conducted using surface challenge test and finally compatibility with other disinfectants was performed to ensure that there is no adverse interaction between them. This new product demonstrated more than 3 log reduction (LR) in less than one minute against tested vegetative bacteria and yeast Bacillus subtilis (>4.68, >4.81, >3.85 and >4.88), Pseudomonas aeruginosa (>4.00, >4.34, >3.85 and >4.04) Candida albicans (>4.11, >4.18, >4.95 and >4.48), Micrococcus lylae (>5.56, >5.56, >5.65 and 5.74) and Leifsonia aquaticum (>5.82, 5.79, >5.75 and >5.74) but about 15min were needed to achieve high log reduction against Aspergillus niger (3.02, 2.94, 2.91 and 3.10) and no remarkable log reduction of bacterial spores of Bacillus subtilis and Bacillus pumilus even after 30min of contact time on coupons inoculated with microorganisms. There is no interaction between this new formula and any other commonly used disinfectants in pharma-ceutical facility. The new disinfectant may be used as sanitizer with good activity but not as sporicidal agent for up to 30min contact time.